La institucionalización de las matemáticas en la Nueva España: 1782-1810 - López Alejandre, Ruth (Universidad Michoacana de San Nicolás de Hidalgo, 2008)
Our investigation settles down in the parameters of the history of the sciences. It is about a history of the mathematics in New Spain during the last two decades of the XVIII century and the first of the XIX one, period in which the modern mathematics elements were introduced through educational institutions created by the Spanish Crown. In a more specific way this it is a history of the teaching of the mathematics that analyzes the instruction from this science to the interior of the three educational more important institutions of the time. In this investigation we have demonstrated that the instruction of the mathematics from the classes of the Real University of Mexico, the Real Academy of San Carlos' Three Noble Arts and the Real Seminar of Mining, depended directly on the necessities and objectives of each one of these educational institutions; giving origin to a range of characteristic own in the teaching-learning processes, with what was of manifesto that the state of knowledge of the mathematics to the interior of the viceroyalty was heterogeneous. The history of the sciences, as branch of the historical discipline, is relatively young, since nevertheless that he/she originated in the XVIII century, during the Illustration, it began its development model low own historiográficos until the sixth decade of the XX century.1 the history of the sciences has you retroalimentado with elements of other average historiográficas; as well as of the different focuses provided by the loving historians of the sciences, for the contributions of the passionate mathematicians for the history and for the philosophers attracted by the science and its history.

Nuestra investigación se establece en los parámetros de la historia de las ciencias. Se trata de una historia de las matemáticas en la Nueva España durante las dos últimas décadas del siglo XVIII y la primera del XIX, periodo en el cual se introdujeron los elementos de la matemática moderna a través de instituciones educativas creadas por la Corona española. De manera más específica esta es una historia de la enseñanza de las matemáticas que analiza la instrucción de esta ciencia al interior de las tres instituciones educativas más importantes de la época. En esta investigación hemos demostrado que la instrucción de las matemáticas desde las cátedras de la Real Universidad de México, la Real Academia de las Tres Nobles Artes de San Carlos y el Real Seminario de Minería, dependió directamente de las necesidades y objetivos de cada una de estas instituciones educativas; dando origen a una gama de características propias en los procesos de enseñanza-aprendizaje, con lo que quedó de manifiesto que el estado de conocimiento de las matemáticas al interior del virreinato fue heterogéneo. La historia de las ciencias, como rama de la disciplina histórica, es relativamente joven, ya que no obstante que se originó en el siglo XVIII, durante la Ilustración, inició su desarrollo bajo modelos historiográficos propios hasta la sexta década del siglo XX.1 La historia de las ciencias se ha retroalimentado con elementos de otras corrientes historiográficas; así como de los diferentes enfoques proporcionados por los historiadores amantes de las ciencias, por los aportes de los matemáticos apasionados por la historia y por los filósofos atraídos por la ciencia y su historia.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-M-2008-0014; Opción en historia de México; Institucionalización; Matemáticas; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2382